2012
DOI: 10.1002/chem.201102987
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Nickel Complexes Derived from 2‐Pyridylcyanoxime: An Approach to the Magnetic Properties of the [Ni33‐OH){pyC(R)NO}3]2+ Core

Abstract: A series of nickel complexes with nuclearity ranging from Ni(3) to Ni(6) have been obtained by treatment of a variety of nickel salts with the 2-pyridylcyanoxime ligand. The reported compounds have as a common structural feature the triangular arrangement of nickel cations bridged by a central μ(3)-oxo/alkoxo ligand. These compounds are simultaneously the first nickel derivatives of the 2-pyridylcyanoxime ligand and the first examples of isolated, μ(3)-O triangular pyridyloximate nickel complexes. Magnetic mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 73 publications
(12 reference statements)
4
13
0
Order By: Relevance
“…In good agreement with previous DFT calculations,6b the isosceles response of the magnetic interactions and structural data from Table 4 suggest that the Ni–O–Ni bond angles correlate with the magnitude of the coupling constants whereas there is no evident correlation with the Ni–O–N–Ni torsion angles. This becomes evident in Figure 7, which shows a linear dependence of J with the Ni–O–Ni bond angle, whereas the plot of J as a function of the Ni–O–N–Ni torsion angle shows very different values of J for similar torsion angles and similar J values for any torsion.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In good agreement with previous DFT calculations,6b the isosceles response of the magnetic interactions and structural data from Table 4 suggest that the Ni–O–Ni bond angles correlate with the magnitude of the coupling constants whereas there is no evident correlation with the Ni–O–N–Ni torsion angles. This becomes evident in Figure 7, which shows a linear dependence of J with the Ni–O–Ni bond angle, whereas the plot of J as a function of the Ni–O–N–Ni torsion angle shows very different values of J for similar torsion angles and similar J values for any torsion.…”
Section: Resultssupporting
confidence: 91%
“…Complexes 1 and 2 are close to magnetically frustrated triangles, whereas complex 3 is an unusual example of an equilateral axial triangle with three‐fold symmetry and the S = 0 ground state. Correlation of the magnetostructural parameters of these three new examples of μ 3 ‐OR/oximato‐Ni 3 isolated triangles and the previously reported6b [Ni 3 (MeOH) 2 (BzO)(OH)(py{CN}NO) 4 ] ( 4 ) and the linked triangles (NEt 3 H){μ 1,5 ‐N(CN) 2 }[Ni 6 (H 2 O)(MeOH)(3‐ClBzO) 2 (OH) 2 (py{CN}NO) 8 ] ( 5 ) has confirmed that the Ni–O–Ni bond angles involving the central RO – bridge are the main factors influencing the magnitude of the superexchange interaction, as was predicted by DFT calculations.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…To compute J, it is therefore very important to be able to tune not only the multiplicity on the different metal centers but also the relative orientation of their net spin (i.e., ferromagnetic or antiferromagnetic coupling). Such a fine tuning is possible in the initial guess algorithm employed in Jaguar, and it is therefore often used in such cases …”
Section: Jaguar Featuresmentioning
confidence: 99%